Factors Influencing Purchase Intention towards International Cosmetic Products among Malay Women - Ilya Syahirah Izani; Syed Ashrene Syed Omar; Azurin Sani; Ahmad Shazeer Mohamed Thaheer; Sharifah Fazirah Syed Ahmad (Information Management and Business Review, 2023)
An attractive appearance is essential for women. Women are willing to spend money for the sake of taking care of their face and skin by buying trusted cosmetic brands. The utilization of cosmetic items has emerged as a significant aspect across the lifespan, from infancy to old age, with a growing number of consumers engaging in the consumption of such products. Consumers in developing countries prefer well-known international products rather than domestic products because they have more confidence in the quality of foreign products. Hence, the researcher aims to investigate the extent to which product quality, packaging, brand name and promotion influence purchase intention toward international cosmetic products among Malay women in Putrajaya Malaysia. Therefore, a survey of 105 Malay women in Putrajaya Malaysia was conducted to analyze the factors that influence purchase intention toward international cosmetic products. Correlation analysis is used to analyze the data to identify the relationship between the variables. Furthermore, multiple regression analysis is used to assess the significant influential factors toward purchase intention.  The result from the survey discovered that only product quality has a significant relationship with purchase intention towards international cosmetic products among Malay women in Putrajaya Malaysia. Packaging, brand name and promotion were not found to have a significant relationship towards purchase intention towards international cosmetic products.